2021
DOI: 10.3390/ijms22041747
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Quantitative Phosphoproteomics of the Fission Yeast Schizosaccharomyces pombe Using Strong Anion Exchange- and Porous Graphitic Carbon-Based Fractionation Strategies

Abstract: The phosphorylation of proteins modulates various functions of proteins and plays an important role in the regulation of cell signaling. In recent years, label-free quantitative (LFQ) phosphoproteomics has become a powerful tool to analyze the phosphorylation of proteins within complex samples. Despite the great progress, the studies of protein phosphorylation are still limited in throughput, robustness, and reproducibility, hampering analyses that involve multiple perturbations, such as those needed to follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In our previous work, we used the tandem affinity purification (TAP) protocol to purify Swi5-TAP and Sfr1-TAP from cycling S. pombe cells and found that Swi5 was phosphorylated on serine 72 and Sfr1 contained three phosphorylated serine residues (S26, S109 and S165) [ 24 ]. Additional phosphorylation sites on Sfr1 (S24, S26, T73, S109, S116 and S165) were published during the course of our work [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we used the tandem affinity purification (TAP) protocol to purify Swi5-TAP and Sfr1-TAP from cycling S. pombe cells and found that Swi5 was phosphorylated on serine 72 and Sfr1 contained three phosphorylated serine residues (S26, S109 and S165) [ 24 ]. Additional phosphorylation sites on Sfr1 (S24, S26, T73, S109, S116 and S165) were published during the course of our work [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that many splicing factors have to be phosphorylated in order to function properly [8,. Although previous studies showed that Nrl1 is phosphorylated on multiple sites (T26, S122, S131 and S970) [49][50][51][52][53], little was known about the importance of these post-translational modifications. Here, by analyzing the isolated Nrl1 complexes we found that Nrl1 is also phosphorylated on residues S86 and S112 (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Nrl1 is phosphorylated on several amino acid residues [42,45,[49][50][51][52][53]. This suggested that, similarly to other splicing factors, the function of Nrl1 might be regulated by phosphorylation.…”
Section: Analysis Of Nrl1 Phosphorylationmentioning
confidence: 97%
“…for PTMs protein sample preparation and enrichment. For example, the enrichment strategies operated in phosphoproteomic studies are molecularly imprinted technology (MIP) [25,26], ion exchange chromatography (IEC) [27][28][29], affinity chromatography [30][31][32], and chemical derivatization [33,34]. Different from phosphorylation modifications with fixed structures, the diversity of polysaccharides and the interference of glycans on the peptide backbone make the identification of glycopeptides and the study of protein glycosylation encounter more obstacles.…”
Section: Introductionmentioning
confidence: 99%